Penguatan Organisasi Sekolah melalui Pendekatan Mutu Terpadu - Farid Hasyim (UIN Maulana Malik Ibrahim Malang, 2003)
The most important of school organizations is to create effective and efficient teaching and learning processes in schools, which are the main task of the school. Without touching on this aspect, the school organization will have no significance in building schools in conducting the education process effectively. Some of the most effective studies that are associated with organizational processes always provide an important part of the role of school management in creating an effective school climate and culture. In this case, parent and student communities should be directly involved in the school management process, especially in the decision-making process. This is done as an effort to increase commitment, ownership and responsibility in peroses education in schools. Yang terpenting dari organisasi sekolah adalah menciptakan proses pengajaran dan pembelajaran secara efektif dan efisien di sekolah, yang merupakan tugas pokok sekolah. Tanpa menyentuh aspek ini, maka organisasi sekolah tidak akan mempunyai arti penting dalam membangun sekolah dalam melakukan proses pendidikan secara efektif. Beberapa penelitian yang efektif yang dikaitkan dengan proses organisasi selalu memberikan bagian penting dari peran manajemen sekolah dalam menciptakan iklim dan kultur sekolah yang efektif. Dalam hal ini, komunitas orang tua dan siswa hendaknya terlibat langsung dalam proses pengelolaan sekolah, terutama dalam proses pembuatan keputusan. Hal ini dilakukan sebagai upaya meningkatkan komitmen, rasa memiliki dan tanggung jawabnya dalam peroses pendidikan di sekolah.